PENGARUH AUDITOR SWITCHING DAN FINANCIAL DISTRESS PADA OPINI AUDIT GOING CONCERN - Setiadamayanthi, Ni Luh Ayu; Wirakusuma, Md. Gd. (E-Jurnal Akuntansi, 2016)
This study was conducted to determine the effect of switching auditors and financial distress in going concern audit opinion. The population in this study are all companies listed on the Indonesia Stock Exchange in 2014. The sampling method used is purposive sampling method. The number of samples used in this study is 44 companies. Data collection methods used in this study is a non-participant observation method. The data analysis technique used to solve the problem is the logistic regression analysis. Based on the results of analysis known that the tendency of switching auditor has no effect on the going concern audit opinion, as well as the likelihood of financial distress do not affect the going concern audit opinion.
Keywords: auditor switching, financial distress, opinion